Problems of ensuring the right of a minor to qualified legal assistance in criminal proceedings - Zhumabayeva, Zh.Zh.; Zhamiyeva, R.M.; Кудрявцева, А.В. (Bulletin of the Karaganda University “Law Series”, 2020)
The purpose of the research in this article is to identify legal and practical problems in the implementation of guaranteed qualified legal assistance to minors involved in criminal proceedings, and to formulate proposals for resolving these problems; development of a comprehensive mechanism for ensuring the right of a minor to qualified legal assistance in criminal proceedings by improving the procedural status of a minor suspect (accused, defendant), a witness entitled to protection, a victim witness, and developing a unified approach to the status of a minor. The use of general and private scientific research methods allowed us to assess the current state, patterns and main trends in the development of the institution of guaranteed legal assistance to minors. The result of the research is the formulation of conclusions about the imperfection of legislative regulation and the existence of gaps in the mechanism for implementing the right of minors to qualified legal assistance. The right of a minor to qualified legal assistance is studied through the prism of the criminal process stages and it is concluded that there are no legal conditions for the implementation of this right at the initial stage of criminal proceedings. The prerequisite for the actual deprivation of a minor of the most important legal guarantee is the artificial removal from the criminal process of part of the legal relationship that develops at the initial stage of a criminal case investigation. The issue of extending the procedural guarantee under consideration to a minor participant, regardless of its specific role and certain procedural status, requires further improvement.